NEGOSIASI PENDIDIKAN ISLAM DAN NEGARA PADA MASA ORDE LAMA KAJIAN HISTORIS MADRASAH DAN PESANTREN - Abdur Rohman; Shodrus Syahid; M. Bustomi; Anang Sholikhuddin (CV. BAROKAH PUBLISHER, 2026)
This study examines the negotiation process between the state and Islamic educational institutions—particularly madrasah and pesantren—during the Old Order period (1945–1965). Employing a historical approach through library research, this study analyzes how government policies toward Islamic education were formulated and how madrasah and pesantren responded through institutional adaptation. The concept of